Acceptance of Culture Mobile Tourism Among Tourist: A Model Development Study - Syaifullah, Syaifullah; Ariffin, Shamsul Arrieya; Nordin, Norhisham Mohamad (Journal of Applied Engineering and Technological Science (JAETS), 2025)
This study is a preliminary study on the development of a new model by combining and integrating existing models, namely the Technology Acceptance Model (TAM) and Hofstede's Culture Dimension. The development of this model was carried out using IPO logic (input-process-output) and a causal model by combining, adopting, and adapting previous models. The influence of the formed path consists of 17 links and produces 10 variables. The existing variables will be formed into 40 indicators. This study examines the impact of cultural values on tourists' perceptions of usefulness, ease of use, trust, and conditions that support mobile tourism technology. This study also investigates the mediating role of cultural dimensions on behavioral intentions to use mobile tourism. This study intends to provide important information in developing and implementing more effective and sensitive mobile tourism by incorporating cultural dimensions into the TAM framework. These findings will provide extensive information to stakeholders about tourism improvement and the importance of cultural adaptation in adopting mobile tourism.